Genome-wide association study for yield and quality of granulated cassava processed product - Aghogho, C.I.; Kayondo, S.I.; Eleblu, S.J.Y.; Ige, A.; Asante, I.; Offei, S.K.; Parkes, E.; Egesi, C.; Mbanjo, E.G.N.; Shah, T.; Kulakow, P.; Rabbi, I.Y. (Wiley, 2024)
The starchy storage roots of cassava are commonly processed into a variety of products, including cassava granulated processed products (gari). The commercial value of cassava roots depends on the yield and quality of processed products, directly influencing the acceptance of new varieties by farmers, processors, and consumers. This study aims to estimate genetic advance through phenotypic selection and identify genomic regions associated and candidate genes linked with gari yield and quality. Higher single nucleotide polymorphism (SNP)-based heritability estimates compared to broad-sense heritability estimates were observed for most traits highlighting the influence of genetic factors on observed variation. Using genome-wide association analysis of 188 clones, genotyped using 53,150 genome-wide SNPs, nine SNPs located on seven chromosomes were significantly associated with peel loss, gari yield, color parameters for gari and eba, bulk density, swelling index, and textural properties of eba. Future research will focus on validating and understanding the functions of identified genes and their influence on gari yield and quality traits.